Pengaruh Fasilitas Terhadap Keputusan Tamu Menginap Di Parkside Nuansa Maninjau Resort - Suci Andriani Putri; Yuliana Yuliana (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research is motivated by the discovery of problems, namely unstable room sales, there are still many guests who do not recommend hotels, many guests cancel room reservations, it is still difficult to get information about hotels and supporting facilities such as inadequate wifi. The purpose of this study was to analyze the effect of facilities on guest decisions to stay at Parkside Nuansa Maninjau Resort. The type of research is quantitative with a causal associative approach involving two variables. The population in this study were guests who had stayed and who were staying at Parkside Nuansa Maninjau Resort. The sample in this study were 298 respondents using purposive sampling technique. The type of data used in this study is primary data collected through distributing questionnaires. The results showed that the hotel facilities were in a fairly good category with a percentage (41%) in the range 29.35-<36.5. The decision of guests to stay is in a fairly good category with a percentage (39.93%) in the range 37.05-<46.65. The results of simple linear regression analysis show an R square value of 0.540, meaning that the effect of hotel facilities on guest decisions staying overnight is 54%. The regression coefficient results show 0.751 with a sig value. 0,000 < 0,05. This means that every increase of 1 unit of facilities will increase 0.751 units of guest decisions to stay.